W poszukiwaniu drogi do emancypacji – oczekiwania niesłyszących - Jagoszewska, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
Many of the questions posed in the discussion on the modern state education policy are those connected with the search for ways of emancipation of deaf. Many issues of practical importance refers to the expectations of the deaf determined by diversity and specificity of their functioning , aspirations for autonomy or complex expectations regarding access to sign language. All this happens with simultaneous constraints to meet existing needs and changes achieved in legislation with a clear increase in the expression of the vital interests of one group in an incoherent community of the deaf.